RETRACTED: Transition processes during the start-up of the pumping unit of happ - Abdulkhaev Z.E.; Madraximov M.M.; Orzimatov J.T.; Abdurazaqov A.M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001